RETRACTED: The Effect of Compensation, Competence, and Work Discipline on The Performance of Employees of PT Harta Kharisma Wanapadu South Jakarta - Gio Vanie; Ahmad Cik; Kumba Digdowiseiso (Journal of Social Science, 2024)
Kharisma Wanapadu, South Jakarta, totaling 100 workers. The instrument tests in this review are coordinated to use validity and reliability tests. The information- checking strategy in this study was coordinated to utilize a variety of direct relapse investigation methods. The results of the review show that the factors of Compensation, Competence, and Work Discipline have a good effect on the presentation of its representatives, at PT.Harta Kharisma Wanapadu, South Jakarta with an importance. The background of this research is to obtain data related to the Impact of Compensation, Competence, and Work Discipline on the Implementation of Representatives at PT.Harta Kharisma Wanapadu, South Jakarta. This study combines quantitative reports, where the research instrument is a questionnaire. The sample in this study were representatives at PT.Harta level below 5%.